The pathway to security – mitigating user negligence. (11th July 2016) - Kennedy, Sarah Elizabeth
Abstract : Purpose: Through the use of effective training techniques and exercises, employees and users can be educated on how to make safe information security decisions. It is critical to the success of a total information security program that users are trained properly as they are a major layer of defense against malicious intent. The current methods of training people about information security are failing, and the number of user-related breaches increases every year. Design/methodology/approach: By researching and observing current methods and comparing other fields of study, this paper describes the best methodology for modifying user behavior as it pertains to information security. Findings: Through effective training practices, user negligence can be mitigated and controlled, and the information security program can be better practiced throughout entire organizations. Originality/value: By using an effective training method to teach employees about information security, employees become an invaluable part of a company's overall information security strategy. By using this method, employees are no longer the weak link in information security.